2021
DOI: 10.5194/cp-17-1273-2021
|View full text |Cite
|
Sign up to set email alerts
|

Climate indices in historical climate reconstructions: a global state of the art

Abstract: Abstract. Narrative evidence contained within historical documents and inscriptions provides an important record of climate variability for periods prior to the onset of systematic meteorological data collection. A common approach used by historical climatologists to convert such qualitative information into continuous quantitative proxy data is through the generation of ordinal-scale climate indices. There is, however, considerable variability in the types of phenomena reconstructed using an index approach an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 227 publications
(321 reference statements)
1
38
0
Order By: Relevance
“…This study set out to explore and quantify the degree of error between individuals generating ordinal-scale climate indices from a historical documentary dataset. Ultimately, our findings reinforce the conclusions of Nash et al (2021) that climate indices should be derived by those with training in historical climatology methods, as well as a detailed knowledge of both the climate of the area in question and the nature of the documentary sources. However, we have demonstrated that generating such indices using groups of two or more researchers will substantially reduce the issue of researcher subjectivity.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This study set out to explore and quantify the degree of error between individuals generating ordinal-scale climate indices from a historical documentary dataset. Ultimately, our findings reinforce the conclusions of Nash et al (2021) that climate indices should be derived by those with training in historical climatology methods, as well as a detailed knowledge of both the climate of the area in question and the nature of the documentary sources. However, we have demonstrated that generating such indices using groups of two or more researchers will substantially reduce the issue of researcher subjectivity.…”
Section: Discussionsupporting
confidence: 81%
“…Raters were also asked to provide a brief explanation of why they assigned each rain-year to a particular category, and a summary of rainfall conditions. This approach to index development represents a variation on the 'Pfister method' (see Pfister et al, 2018;Nash et al, 2021), using five categories rather than seven, and generating a series for an entire season rather than monthly. Training Partnership.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Historical texts, both descriptive sources, such as chronicles, and written records of phenology, such as grape harvest dates, have enabled high-resolution reconstructions of temperature and precipitation for periods prior to the modern instrumental record (White et al, 2018). The principal approach for these reconstructions has been the "index" method (Pfister et al, 2018;Nash et al, 2021). Historical climatologists working with these texts have converted their information into ordinal indices (typically -3 to +3), which approximate departures from average monthly or seasonal conditions, and they have calibrated these indices to early instrumental data to obtain reconstructed values for the pre-instrumental period.…”
Section: Introductionmentioning
confidence: 99%